Living in Agreement with a Contract: The Management of Moral and Viable Firm–Stakeholder Relationships - Pajunen, Kalle (Journal of business ethics, 2006)
In a contractual firm–stakeholder relationship the participants are expected to act according to the agreement and for mutual benefit. By acting against the agreement at the expense of the other participant, however, may result in higher individual profits within a short period of time. Building on the unlocked iterated prisoner’s dilemma (PD) setting, Scanlon’s [Scanlon, T.␣M.: 1998, What We Owe to Each Other (Belknap Press of Harvard University Press, Cambridge, Mass)] version of contractualism, and the social dilemma literature, this article considers what types of behaviors should be followed by both parties in an established firm–stakeholder relationship in order to reach an outcome that is defensible both in terms of morality and viability. It is argued that a normative foundation, which advises firms and stakeholders to ground their behavior on principles that could not reasonably be rejected by others, forms a basis for moral and viable behavior that can be expressed in the form of a strategic rule that excludes defection and utilizes the option to exit in response to the other participant’s defection. Then, a set of testable propositions is developed that describe how a firm and its stakeholders can further promote moral and viable relationships.